Junctional Bradycardia dengan Sindrom Kardiorenal - Kabanga, Yehiel Flavius; Haryana, Iman; Jolanda, Denny; Patandean, Alvionita (Cermin Dunia Kedokteran, 2024)
Junctional bradycardia occurs when electrical activity at the SA node is disrupted, or there is a conduction block originating from the SA node, or its automaticity is less than the AV node or HIS bundle. A 46-year-old female was referred because of shortness of breath and swollen limbs. The patient has a long history of diabetes and hypertension. She was diagnosed with acute pulmonary edema, junctional bradycardia, stage 4 CKD, CHF, hypoalbuminemia, anemia, and T2DM. The patient was admitted to the ICCU for 7 days before being discharged. Cardiorenal syndrome can induce sinus node dysfunction or AV node dysfunction, leading to junctional bradycardia. Subsequently, the junctional bradycardia exacerbates concomitant heart failure and renal failure.